X-ray Free Electron Laser Accelerator Lattice Design Using Laser-Assisted Bunch Compression - Haoran Xu; Petr M. Anisimov; Bruce E. Carlsten; Leanne D. Duffy; Quinn R. Marksteiner; River R. Robles (Applied Sciences, 2023)
We report the start-to-end modeling of our accelerator lattice design employing a laser-assisted bunch compression (LABC) scheme in an X-ray free electron laser (XFEL), using the proposed Matter-Radiation Interactions in Extremes (MaRIE) XFEL parameters. The accelerator lattice utilized a two-stage bunch compression scheme, with the first bunch compressor performing a conventional bulk compression enhancing the beam current from 20 A to 500 A, at 750 MeV. The second bunch compression was achieved by modulating the beam immediately downstream of the first bunch compressor by a laser with 1-<semantics>μm</semantics> wavelength in a laser modulator, accelerating the beam to the final energy of 12 GeV, and compressing the individual 1-<semantics>μm</semantics> periods of the modulated beam into a sequence of microbunches with 3-kA current spikes by the second bunch compressor. The LABC architecture presented had been developed based on the scheme of enhanced self-amplified spontaneous emission (ESASE), but operated in a disparate regime of parameters. Enabled by the novel technology of the cryogenic normal conducting radiofrequency photoinjector, we investigated an electron beam with ultra-low emittance at the starting point of the lattice design. Our work aimed at mitigating the well-known beam instabilities to preserve the beam emittance and suppress the energy spread growth.